'Employability in context': The importance of considering contextual factors in reimagining employability through Australian student mobility to the Indo‐Pacific region. (1st February 2021) - Thi Tran, Ly; Thi Quy Do, Thu; Bui, Huyen
Abstract: Australia has shifted its student mobility agenda since 2014 with a commitment to see learning abroad in the Indo‐Pacific region, rather than in traditional destinations such as anglophone countries, as a 'rite of passage' for Australian students' future life and career. While there has been rich literature on the impact of outbound student mobility from Australia to anglophone countries, critical inquiry is warranted regarding how Australian students' learning abroad in the Indo‐Pacific affects their employability and career directions. This article responds to this paucity in the literature. It is derived from a larger research project, including a survey of 1, 362 New Colombo Plan alumni. Unlike dominant conceptualisations of employability focusing largely on the role of disciplinary knowledge and soft skills, this study found affording different perspectives, connections and opportunities and the increased knowledge about the Indo‐Pacific have been critical in shaping Australian students' employability and career orientations. The findings of this study provide the empirical base for the development of the concept, 'employability in context', which underscores the importance of moving beyond the conventional discourse about employability and taking into account the contextual factors in conceptualising employability. Tóm lược: Bài báo nghiên cứu tác động của việc du học và thực tập ngắn hạn của sinh viên Úc tại khu vực Ấn Độ Dương ‐ Thái Bình Dương đến năng lực tìm việc làm và định hướng nghề nghiệp của sinh viên. Bài báo này là một phần trong dự án nghiên cứu, bao gồm khảo sát đối với 1, 362 sinh viên của chương trình New Colombo Plan (NCP) của chính phủ Úc. Nghiên cứu cho thấy mối liên hệ với cộng đồng nơi sinh viên đến học và kiến thức chuyên sâu về khu vực Ấn Độ Dương ‐ Thái Bình Dương có ảnh hướng lớn đến năng lực tìm việc làm và định hướng nghề nghiệp của sinh viên. Những kết quả nghiên cứu này là cơ sở thực nghiệm hình thành khái niệm mới, "năng lực tìm việc làm theo bối cảnh". Bài báo nhấn mạnh tầm quan trọng của việc vượt ra khỏi những khái niệm truyền thống về năng lực tìm kiếm việc làm và sự cần thiết phải xem xét các yếu tố bối cảnh trong việc hình thành nên khái niệm này.